Risk management in minimizing KPR Bank BTN Syariah kcps probolinggo financing - Sitti Aisyah; Abu Yazid Adnan Qudni; Ahmad Fajri (Institute of Computer Science (IOCS), 2023)
One of the businesses engaged in Islamic banking where money is stored and given to those in need is Bank BTN Syariah. Bank BTN Syariah must make a decision in allocating home ownership financing after determining the eligibility of the debtor's application. This assessment is carried out to assist Bank BTN Syariah in preventing risks or losses related to unreturned loans. To prevent the dangers of problematic financing, bank BTN Syariah adheres to the 5C principle, namely the characteristics of capacity, capital, collateral and economic conditions. In addition, he uses a plan that includes a grace period (delay), principal balance rescheduling, and outstanding balance rescheduling. In this investigation, we will find out how the risk management of BTN Syariah KPR products can reduce troubled bank funding. This study uses a qualitative descriptive methodology, which is used to collect data is literature study, field research using observation or observations, interviews, and documentation. The study findings show that there are risks related to mortgage products at Bank BTN Syariah arising from debtor failures which result in non-fulfillment of debt payment obligations. As a result, banks must have risk management to minimize these risks effectively so that losses do not occur.